The coincidence of IgA nephropathy and Fabry disease - Maixnerová, Dita; Tesař, Vladimír; Ryšavá, Romana; Reiterová, Jana; Poupětová, Helena; Dvořáková, Lenka; Goláň, Lubor; Neprašová, Michaela; Kidorová, Jana; Merta, Miroslav; Honsová, Eva (BMC nephrology, 2013)
BACKGROUND: IgA nephropathy (IgAN) is the most common glomerulonephritis, which may also coexist with other diseases. We present two patients with an unusual coincidence of IgAN and Fabry disease (FD). CASE PRESENTATION: A 26 year-old man underwent a renal biopsy in February 2001. Histopathology showed very advanced IgAN and vascular changes as a result of hypertension. Because of his progressive renal insufficiency the patient began hemodialysis in August 2001. By means of the blood spot test screening method the diagnosis of FD was suspected. Low activity of alpha-galactosidase A in the patient's plasma and leukocytes and DNA analysis confirmed the diagnosis of FD. Enzyme replacement therapy started in July 2004. Then the patient underwent kidney transplantation in November 2005. Currently, his actual serum creatinine level is 250 μmol/l. Other organ damages included hypertrophic cardiomyopathy, neuropathic pain and febrile crisis. After enzyme replacement therapy, myocardial hypertrophy has stabilized and other symptoms have disappeared. No further progression of the disease has been noted.The other patient, a 30 year-old woman, suffered from long-term hematuria with a good renal function. Recently, proteinuria (2.6 g/day) appeared and a renal biopsy was performed. Histopathology showed IgAN with remarkably enlarged podocytes. A combination of IgAN and a high suspicion of FD was diagnosed. Electron microscopy revealed dense deposits in paramesangial areas typical for IgAN and podocytes with inclusive zebra bodies and myelin figures characteristic of FD. FD was confirmed by the decreased alpha-galactosidase A activity in plasma and leukocytes and by DNA and RNA analysis. Enzyme replacement therapy and family screening were initiated. CONCLUSIONS: Our results emphasize the role of complexity in the process of diagnostic evaluation of kidney biopsy samples. Electron microscopy represents an integral part of histopathology, and genetic analysis plays a more and more important role in the final diagnosis, which is followed by causal treatment.
Keywords: Fabryho nemoc; Fabry Disease; Adult; Male; Diagnosis, Differential; dospělí; lidé; mužské pohlaví; ženské pohlaví; Female; IgA nefropatie; Humans; Glomerulonephritis, IGA; diferenciální diagnóza